On the Gaussian Random Matrix Ensembles with Additional Symmetry Conditions - Vasilchuk, V. (Symmetry, Integrability and Geometry: Methods and Applications, 2006)
The Gaussian unitary random matrix ensembles satisfying some additional symmetry conditions are considered. The effect of these conditions on the limiting normalized counting measures and correlation functions is studied.